Mathematical model of optimal placement of a hybrid power plant with a combined cycle - Ahmed Z. Abass; D. A. Pavlyuchenko; V. M. Less (Известия высших учебных заведений: Проблемы энергетики)
PURPOSE. Purpose of the Work - To build a hybrid solar power plant and a gas turbine plant (ISCC), several important elements must be available. Making a decision in principle to build a hybrid power plant and determining its optimal location requires an analysis of many factors in Iraq. Iraq is a region rich in solar energy. Solar energy potential from an area of 437,072 km2 exceeds the current demand for electricity by hundreds of thousands of times. This will help Iraq to remain an energy exporter in the future by switching from fossil fuels to solar energy. METHOD- Determines the relevance of research in this area, namely the development of a multivariate mathematical model for finding the optimal location of a ISCC using the method of paired comparisons using the MATLAB program. RESULTS - Province Albasra is characterized by a significantly higher level of electricity consumption in the region, as well as a more developed infrastructure. This, in general, predetermines the highest final rating among all the provinces of Iraq as the optimal region for the location of a ISCC. CONCLUSION- Using the proposed mathematical model, a rating was calculated and a comparison was made of the provinces of Iraq to determine the best region for placing such ISCC. This mathematical model can be used for further localization of the solution to the problem, for example, when considering the best conditions for the construction of a hybrid power plant already within a province, etc.